A great little ally: revealing the morphology of the immature stages of the aphid pest predator Sphaerophoria rueppellii (Wiedemann, 1830) (Diptera: Syrphidae). Issue 1 (31st December 2022) - Orengo-Green, J. J.; Kanturski, M.; Ricarte, A.; Marcos-García, Mª. Á.
Abstract: Morphology, at both adult and larval stages is crucial for the correct identification of an insect and a better understanding of its biology and behaviour. The lack of morpho-functional information in insects is much more general in the immature stages than in adults, and major insect orders, such as Diptera are no exception. Syrphids (Diptera: Syrphidae) include various genera with aphidophagous larvae playing a key role in the control of pest insects in both natural and agricultural systems. The aphidophagous Sphaerophoria rueppellii (Wiedemann, 1830) is a syrphid widely distributed in the Palearctic Region and it is of commercial importance as a biological control agent against aphid pests. However, little is known about the fine morphology of its immature stages because it was described in 1939, when microscopy did not allow detailed studies of certain morphological features. In this work, stereomicroscope and scanning electron microscopy (SEM) were used to get a deeper and more detailed picture of the immature stage morphology of this syrphid. SEM was used to examine in detail the chaetotaxy of three larval instars, the larva/puparium posterior respiratory process (PRP), and the chorionic structure of the egg. We describe for the first time the egg, first and second larval stages, and also give a complete updated description of the third-stage larva and the puparium. The three larval instars vary from each other, especially in the number of sensillae, PRP form, colour, and body size. The thickness of both the egg chorion and puparium integument were also measured. A possible interpretation of the reasons for the variability in the number of sensillae is discussed. Illustrations and full descriptions are provided for the egg, larva, and puparium of S. rueppellii, including the head skeleton of the third larval stage.